Synergistic actions of Alpelisib and Melatonin in breast cancer cell lines with PIK3CA gene mutation - de Godoy, Bianca Lara Venâncio; Moschetta-Pinheiro, Marina Gobbe; Chuffa, Luiz Gustavo de Almeida [UNESP]; Pondé, Noam Falbel; Reiter, Russel J.; Colombo, Jucimara; Zuccari, Debora Aparecida Pires de Campos [UNESP] (Elsevier, 2023)
Aims: Breast cancer (BC) presents high mortality rate and about 25–46 % have mutation in the PIK3CA gene. Alpelisib is a PI3K inhibitor that acts on p110α, which is a subunit of the PI3K protein. The melatonin shown important anti-neoplastic effects and may increase the effectiveness of chemotherapy. This study evaluated the synergistic action of Alpelisib and Melatonin in BC lines carrying the H1047R mutation in PIK3CA, relative to the cellular dynamics and the PI3K/AKT/mTOR pathway. Main methods: MDA-MB-468 (triple-ernegative), MDA-MB-453 (H1047R PIK3CA, HER2+) and T-47D cells (H1047R PIK3CA, ER+/PR+) were divided into four treatment groups: control; Melatonin (1 mM); Alpelisib (1 μM); and Alpelisib (1 μM) + Melatonin (1 mM). Cell viability and migration were investigated using the MTT assay and Transwell assay, respectively. Protein expression of PI3K, p-AKT, mTOR, HIF-1α, and caspase-3, was verified using immunocytochemistry. Key findings: MTT assay revealed that MDA-MB-453 and T-47D showed reduction in cell viability in all groups, especially in the MDA-MB-453 treated with Melatonin + Alpelisib. MDA-MB-468 presents reduction in cell migration only with Melatonin, while in the lines with mutation, the treatment of Melatonin + Alpelisib caused inhibition of cell migration. PI3K, p-AKT, mTOR and HIF-1α were inhibited after treatment with Melatonin + Alpelisib in MDA-MB-453 and T-47D lines. The expression of caspase-3 increased in all groups in MDA-MB-453 and T-47D cells, being the increase more pronounced in the Melatonin + Alpelisib group. Significance: These results indicate that the combined use of Melatonin and Alpelisib may be more effective in inhibiting BC in women carrying the PIK3CA gene mutation than either treatment alone.
Keywords: Alpelisib; Breast Cancer; MDA-MB-453; Melatonin; PIK3CA; T-47D